Nanoseconds molecular dynamics simulation of primary mechanical energy transfer steps in F1-ATP synthase. - Böckmann, Rainer; Grubmüller, Helmut (Nature Structural Biology, 2002)
The mitochondrial membrane protein FoF1-ATP synthase synthesizes adenosine triphosphate (ATP), the universal currency of energy in the cell. This process involves mechanochemical energy transfer from a rotating asymmetric gamma-'stalk' to the three active sites of the F1 unit, which drives the bound ATP out of the binding pocket. Here, the primary structural changes associated with this energy transfer in F1-ATP synthase were studied with multi-nanosecond molecular dynamics simulations. By forced rotation of the gamma-stalk that mimics the effect of proton motive Fo-rotation during ATP synthesis, a time-resolved atomic model for the structural changes in the F1 part in terms of propagating conformational motions is obtained. For these, different time scales are found, which allows the separation of nanosecond from microsecond conformational motions. In the simulations, rotation of the gamma-stalk lowers the ATP affinity of the betaTP binding pocket and triggers fast, spontaneous closure of the empty betaE subunit. The simulations explain several mutation studies and the reduced hydrolysis rate of gamma-depleted F1-ATPase.